1985
DOI: 10.1002/jcp.1041230317
|View full text |Cite
|
Sign up to set email alerts
|

Transport by the (Na+, K+) ATPase: Modulation by differentiation inducers and inhibition of protein synthesis in the MDCK kidney epithelial cell line

Abstract: MDCK kidney epithelial cell cultures exposed to the differentiation inducer hexamethylene bisacetamide (HMBA) for 24 hours exhibited a 50% decrease in transport activity per (Na+,K+)-ATPase molecule (turnover number) but an unchanged number of pump sites (Kennedy and Lever, 1984). Inhibition of protein synthesis by either 10 microM cycloheximide or 2 microM emetine blocked the inhibitory effects of HMBA on Na+/K+ pump efficiency assessed by measurements of [3H]-ouabain binding to intact cells, (Na+,K+) ATPase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Some authors reported ouabain binding site in MDCK similar to ours (27). A rather low turnover rate in MDCK cells has been also previously reported (21). It may be speculated that ATP concentration in MDCK cells, but not in HEK, is limiting for Na-K-ATPase activity, in keeping with the previously demonstrated effect of adducin that increases Na-K-ATPase activity by enhancing the affinity for ATP (11).…”
Section: Discussionsupporting
confidence: 56%
“…Some authors reported ouabain binding site in MDCK similar to ours (27). A rather low turnover rate in MDCK cells has been also previously reported (21). It may be speculated that ATP concentration in MDCK cells, but not in HEK, is limiting for Na-K-ATPase activity, in keeping with the previously demonstrated effect of adducin that increases Na-K-ATPase activity by enhancing the affinity for ATP (11).…”
Section: Discussionsupporting
confidence: 56%
“…Several studies in animals demonstrate a reduction in Na + - K + - ATPase activity in heart (Poole et al, 1984) and brain (Poole et al, 1984; Tanaka and Ando, 1990) tissue with added support in human erythrocytes (Poehlman et al, 1993) and lymphocytes (Witkowski et al, 1985). Although there is some conflicting evidence (Kennedy and Lever, 1985), the predominance of evidence suggests a reduction Na + - K + - ATPase that may contribute to the reduction in RMR seen with aging.…”
Section: Total Energy Expenditure and Agingmentioning
confidence: 99%
“…This is achieved after a 24-hr incubation with inducers, requires de novo protein synthesis, and involves a 30 to 40% reduction in the transport efficiency of the Na,K-ATPase (6,19). The significance of this finding is underscored by the observation that inducerresistant variants were refractory to pump inhibition by HMBA (18 differentiation therapy (23).…”
Section: Mechanism Of Action Of Inducersmentioning
confidence: 99%